Cytotoxicity Evaluation of Taverniera spartea on Human Cancer Cell Lines - F Khalighi-Sigaroodi; M Jeddi-Tehrani; M Ahvazi; S Shahnazi; AA Bayat; N Mohajer; S Zarei (Institue of Medicinal Plants, ACECR, 2014)
Background: For centuries, plants have been a major source for drug discovery. Some examples of anticancer agents developed from plants are the vinblastine, vincristine, taxol and camptothecin. Breast cancer is one of the most commonly diagnosed cancers among women and prostate cancer remains a considerable health problem for men around the world. Objective: The purpose of this study was cytotoxicity evaluation of Taverniera spartea on human cancer cell lines. Methods: In the present study, we determined the cytotoxic effects of total methanol extracts and their fractions of Taverniera spartea on MCF-7 and BT-474 human breast cancer cells and also PC-3 and Du-145 prostate cancer cells. Cytotoxicity was evaluated by MTT assay and flow cytometry analysis. Results: The chloroform fraction of Taverniera spartea showed the highest toxicity MTT assay. The IC50 value of this fraction was 70.69 µg/ml for MCF-7 breast cancer cell line after 48 h of exposure. Chloroform fraction showed necrotic effects on MCF-7, BT-474 and PC-3 in contrast apopthotic induction on Du-145 in flow cytometry analysis Conclusion: Taverniera spartea has cytotoxic effects. Further investigation is needed to determine chemical characterization of the active principles and the molecular mechanisms mediated anticancer activities of Taverniera spartea.